2023
DOI: 10.1111/geb.13795
|View full text |Cite
|
Sign up to set email alerts
|

Human modification of land cover alters net primary productivity, species richness and their relationship

Shuyu Deng,
Colin M. Beale,
Philip J. Platts
et al.

Abstract: AimHumans have altered ecosystem productivity and biodiversity worldwide by changing land‐cover types and management. High local species richness is commonly found in geographic areas and ecosystems with high net primary productivity (NPP), but the long‐term effects of modification on productivity and biodiversity change, and particularly on the relationship between the two, are poorly understood. Here we evaluate whether human modification tends to increase biodiversity in low‐productivity ecosystems (where h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Furthermore, a global review of land-use effects on plant species richness found a positive trend in managed grasslands compared to natural habitats (Gerstner et al 2014). Additionally, recent research indicates that global median species richness may either increase or remain stable when comparing different types of natural forests (namely, natural deciduous broadleaf forest, evergreen needleleaf forests, and mixed forests, which are the same natural forests considered in our study) to minor or major human modification (Deng et al 2024). Furthermore, Flynn et al .…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, a global review of land-use effects on plant species richness found a positive trend in managed grasslands compared to natural habitats (Gerstner et al 2014). Additionally, recent research indicates that global median species richness may either increase or remain stable when comparing different types of natural forests (namely, natural deciduous broadleaf forest, evergreen needleleaf forests, and mixed forests, which are the same natural forests considered in our study) to minor or major human modification (Deng et al 2024). Furthermore, Flynn et al .…”
Section: Discussionmentioning
confidence: 90%
“…The contribution of construction land expansion (artificial greening) for construction purposes is 5.4%. Since the inception of the second phase of the TNSFP in 2001, there has been a gradual vegetation recovery and a notable enhancement in the ecological environment, exemplified by the decline in PM2.5 levels and the augmentation of soil conservation efforts [69][70][71].…”
Section: The Influence Of Human Activities On Vegetation Nppmentioning
confidence: 99%